Compression Stockings Used During Two Soccer Matches Improve Perceived Muscle Soreness and High-Intensity Performance. Issue 7 (July 2021) - Gimenes, Samuel Valencia; Marocolo, Moacir; Pavin, Larissa Neves; Spigolon, Leandro Mateus Pagoto; Barbosa Neto, Octávio; da Silva, Bruno Victor Côrrea; Duffield, Rob; da Mota, Gustavo Ribeiro
Abstract : Abstract: Gimenes, SV, Marocolo, M, Pavin, LN, Pagoto Spigolon, LM, Neto, OB, Côrrea da Silva, BV, Duffield, R, and Ribeiro da Mota, G. Compression stockings used during two soccer matches improve perceived muscle soreness and high-intensity performance. J Strength Cond Res 35(7): 2010–2017, 2021—Evidence on the use of compression stockings (CS) during soccer matches is limited. Thus, we evaluated the acute effects of CS on match-based physical performance indicators and perceptual responses during 2 consecutive soccer matches with 72-hour recovery. Twenty outfield players were randomly allocated to the CS group (20–30 mm Hg) or control group (non-CS) and performed 2 matches (5 players using CS or regular socks per team/match). Match loads {rating of perceived exertion × minutes; CS ∼830 vs. control 843 (arbitrary units [AU])} and heart rate (HR) responses (both CS and control ∼86% HRpeak) did not differ ( p > 0.05) between CS and control groups. Although total distance covered did not differ ( p > 0.05) between groups, CS increased distances (effect size [ES] = 0.9–1.32) in higher-speed zones (>19 km·h −1 CS ∼550 m vs. control ∼373 m) alongside an increased number of accelerations (−50.0 to −3.0 m·s −2 ) than control (CS: 33.7 ± 11.2 vs. control: 23.8 ± 7.9; p = 0.003; ES = 1.04). Perceived recovery did not differ ( p > 0.05) between groups for either match but was worse in the second match for both groups. Perceived muscle soreness increased in control after match 2 (from 3.1 ± 1.9 to 6.3 ± 1.6 AU; p < 0.0010) but did not in CS (from 2.8 ± 1.4 to 4.1 ± 1.9 AU; p = 0.6275; ES = 1.24 CS vs. control after match). Accordingly, CS use during 2 soccer matches with 72-hour recovery reduces perceived muscle soreness in the second match and increases higher-speed match running performance.